2022
DOI: 10.1002/tafs.10365
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Temperature and Simulated Angling on the Physiological Stress Response of Largemouth Bass

Abstract: The Largemouth Bass Micropterus salmoides, a popular sport fish, is subjected to multiple sublethal stressors during angling, including high water temperature, exercise, handling, live‐well retention, and weigh‐in procedures. Combined effects of ambient and live‐well temperatures on the stress response and recovery from angling‐induced exercise have not been tested in conditions similar to those encountered in tournaments. Therefore, we assessed the effects of ambient temperature (17, 25, and 33°C) and live‐we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…For recovery to occur, it is important for lactate to be reduced and muscle glycogen to be replenished (Girard and Milligan 1992). One means of recovery from exercise is via muscle glycogenesis, whereby blood lactate is converted back into glycogen via the glycolysis cycle (Dinken et al 2022). When an angling event occurs, glucose is mobilized into the bloodstream, supplying energy for aerobic tissues (e.g., brain and gills; Barton and Iwama 1991), which clearly occurred for the LMB retained in live wells for our study.…”
Section: Discussionmentioning
confidence: 99%
“…For recovery to occur, it is important for lactate to be reduced and muscle glycogen to be replenished (Girard and Milligan 1992). One means of recovery from exercise is via muscle glycogenesis, whereby blood lactate is converted back into glycogen via the glycolysis cycle (Dinken et al 2022). When an angling event occurs, glucose is mobilized into the bloodstream, supplying energy for aerobic tissues (e.g., brain and gills; Barton and Iwama 1991), which clearly occurred for the LMB retained in live wells for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most informative blood variable in this study was pH, which was highest at low temperature and low salinity but also elevated at low temperature and high salinity. Acid-base balance, which is indicated by blood pH, is extremely important to physiological processes, and extreme pH has been related to temperature effects on survival in other species (Dinken et al, 2022;Smit et al, 1981;Stewart et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most informative blood variable in this study was pH, which was highest at low temperature and low salinity but also elevated at low temperature and high salinity. Acid–base balance, which is indicated by blood pH, is extremely important to physiological processes, and extreme pH has been related to temperature effects on survival in other species (Dinken et al ., 2022; Smit et al ., 1981; Stewart et al ., 2019). Blood pH is known to generally relate inversely to temperature ( e.g ., decrease with increasing temperature) in water‐breathing and air‐breathing fishes (Cameron, 1978; Howell et al ., 1970; Rahn & Baumgardner, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, few studies have documented this relationship and have only done so in black basses ( Micropterus spp. , Kieffer et al, 1995 ; Dinken et al, 2022 ). Furthermore, Gallagher et al (2014) found that fight time could not predict blood pCO 2 levels in several shark species.…”
Section: Discussionmentioning
confidence: 99%